Netrin-4 expression by human endothelial cells inhibits endothelial inflammation and senescence. (May 2021) - Zhang, Huayu; Vreeken, Dianne; Leuning, Danielle G.; Bruikman, Caroline S.; Junaid, Abidemi; Stam, Wendy; de Bruin, Ruben G.; Sol, Wendy M.P.J.; Rabelink, Ton J.; van den Berg, Bernard M.; van Zonneveld, Anton Jan; van Gils, Janine M.
Abstract: Netrin-4, recognized in neural and vascular development, is highly expressed by mature endothelial cells. The function of this netrin-4 in vascular biology after development has remained unclear. We found that the expression of netrin-4 is highly regulated in endothelial cells and is important for quiescent healthy endothelium. Netrin-4 expression is upregulated in endothelial cells cultured under laminar flow conditions, while endothelial cells stimulated with tumor necrosis factor alpha resulted in decreased netrin-4 expression. Targeted reduction of netrin-4 in endothelial cells resulted in increased expression of vascular cell adhesion molecule 1 and intercellular adhesion molecule 1. Besides, these endothelial cells were more prone to monocyte adhesion and showed impaired barrier function, measured with electric cell-substrate impedance sensing, as well as in an 'organ-on-a-chip' microfluidic system. Importantly, endothelial cells with reduced levels of netrin-4 showed increased expression of the senescence-associated markers cyclin-dependent kinase inhibitor-1 and -2A, an increased cell size and decreased ability to proliferate. Consistent with the gene expression profile, netrin-4 reduction was accompanied with more senescent associated β-galactosidase activity, which could be rescued by adding netrin-4 protein. Finally, using human decellularized kidney extracellular matrix scaffolds, we found that pre-treatment of the scaffolds with netrin-4 increased numbers of endothelial cells adhering to the matrix, showing a pro-survival effect of netrin-4. Taken together, netrin-4 acts as an anti-senescence and anti-inflammation factor in endothelial cell function and our results provide insights as to maintain endothelial homeostasis and supporting vascular health.